Pengembangan Paket Pembelajaran Ilmu Pengetahuan Sosial (IPS) Kelas IV Menggunakan Model Dick, Carey & Carey di SD Negeri 2 Tamanagung - Riza Faishol (Tarbiyatuna Kajian Pendidikan Islam, 2018)
The purpose of this development is to produce a package of learning materials in the form of learning, teacher's Guide, guide students who are expected to guide the teacher in the learning process that is effective, efficient, and has a fascination for students. Also able to guide and facilitate students to study social science independently. Development model used in this study is a model of Dick, Carey, & Carey have been modified based on the purposes of development. This model leads to learning and problem solving efforts hard-wired through the procedures or steps systematic activities. These steps are 1) identified the need to determine the General purpose learning; 2) performs the analysis of learning; 3) identified the characteristics of the students; 4) formulate specific learning objectives; 5) develop assessment instruments; 6) developing learning strategies; 7) develop and select learning materials; 8) design and implement a formative evaluation; and 9) revise the learning product. Based on the results of the study it can be concluded that the existence of social science learning package class IV semester 1 with Dick, Carey, and Carey has been able to increase student learning results compared to the previous condition. It was apparent from the results of testing the effectiveness of learning using the t test of the pretest and posttest results given to students demonstrating the value of thitung = 64.510 > ttabel = 2.064 so that it can be said that the package of learning science social class IV in SD Negeri 2 Tamanagung subdistrict of Banyuwangi Regency Cluring the year 2012 effective.